Shift in dominant genotypes of Japanese encephalitis virus and its impact on current vaccination strategies - Qiqi Xia; Yang Yang; Yan Zhang; Yan Zhang; Lujia Zhou; Xiaochun Ma; Changguang Xiao; Junjie Zhang; Zongjie Li; Ke Liu; Beibei Li; Donghua Shao; et al. (Frontiers in Microbiology, 2023)
Japanese encephalitis (JE) is a zoonotic ailment from the Japanese encephalitis virus (JEV). JEV belongs to the flavivirus genus and is categorized into a solitary serotype consisting of five genetically diverse genotypes (I, II, III, IV, and V). The JEV genotype III (GIII) was the prevailing strain responsible for multiple outbreaks in countries endemic to JEV until 1990. In recent years, significant improvements have occurred in the epidemiology of JE, encompassing the geographical expansion of the epidemic zone and the displacement of prevailing genotypes. The dominant genotype of the JEV has undergone a progressive shift from GIII to GI due to variations in its adaptability within avian populations. From 2021 to 2022, Australia encountered an epidemic of viral encephalitis resulting from infection with the GIV JEV pathogen. The current human viral encephalitis caused by GIV JEV is the initial outbreak since its initial discovery in Indonesia during the late 1970s. Furthermore, following a time frame of 50 years, the detection and isolation of GV JEV have been reported in Culex mosquitoes across China and South Korea. Evidence suggests that the prevalence of GIV and GV JEV epidemic regions may be on the rise, posing a significant threat to public safety and the sustainable growth of animal husbandry. The global approach to preventing and managing JE predominantly revolves around utilizing the GIII strain vaccine for vaccination purposes. Nevertheless, research has demonstrated that the antibodies generated by the GIII strain vaccine exhibit limited capacity to neutralize the GI and GV strains. Consequently, these antibodies cannot protect against JEV challenge caused by animal GI and GV strains. The limited cross-protective and neutralizing effects observed between various genotypes may be attributed to the low homology of the E protein with other genotypes. In addition, due to the GIV JEV outbreak in Australia, further experiments are needed to evaluate the protective efficiency of the current GIII based JE vaccine against GIV JEV. The alteration of the prevailing genotype of JEV and the subsequent enlargement of the geographical extent of the epidemic have presented novel obstacles in JE prevention and control. This paper examines the emerging features of the JE epidemic in recent years and the associated problems concerning prevention and control.